EFFECTIVE STRATEGIES FOR GROUP WORK IN ENGINEERING CURRICULA - KELLY, KEVIN (My University, 2015)
Modern engineers are expected to be able to work effectively in teams and accreditation criteria (e.g. Engineers Ireland [1], ABET - Accreditation Bureau for Engineering and Technology [2]) typically make explicit reference to these competencies at both an individual and programme level. However, assessment at university has traditionally been performed at the individual level, and many difficulties are regularly noted by engineering educators when trying to manage group projects. These difficulties include equity of marking, balance between individually and collectively assessed components, provision of appropriate levels of guidance and intervention in managing group dynamics, and over- discretization of marking leading to selective targeting by students at the expense of higher order module level learning outcomes. This work reports on two group-design, project-based modules taught in the author’s institution, and a number of specific strategies that have been put in place to address the difficulties noted above. One of the modules is a 5 ECTS [3] second year module and the other is a larger 20 ECTS module taught in fourth year. The rationale behind the implementation of the strategies is noted and results from an end-of year student survey are discussed, to examine the efficacy of these strategies in addressing the commonly encountered difficulties so typical of these types of projects.
32nd International Manufacturing Conference
PUBLISHED
Queens University Belfast
Keywords: Education; Assessment; Groupwork